Electrosynthesis of α-Fe2O3 in a Fe(s)|KCl(aq)||H2O(aq)|C(s) System - Nia Siskawati; Didik Setiyo Widodo; Wasino Hadi Rahmanto; Linda Suyati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Research on α-Fe2O3 electrosynthesis has been performed in the system Fe(s)|KCl(aq)||H2O(aq)|C(s). Electrolysis produces a reduction and oxidation reaction so that it requires a proper electrolyte concentration in the process. The purpose of this study was to obtain α-Fe2O3 compounds, determine the products produced by FTIR and XRD, and determine the size of the grains of products with PSA. Electrolysis method of two compartment was used in this research. The cathode and anode compartments was connected with the salt bridge. In anode chamber containing electrolyte solution KCl was varied (0,2 M; 0,3 M; 0,4 M; 0,5 M and 0,6 M) whereas at cathode space there was aquades. Electrolysis was run at 12 V for 8 hours. The electrolysis result was then calcined for two hours at a temperature of 500°C. The resulting product was then characterized by (FTIR, XRD, and PSA). The resulting product is then characterized by (FTIR, XRD, and PSA). The results showed that brown ferrihydrite was obtained in a concentration of 0.2 M; 0.3 M; 0.4 M; 0.5 M and 0.6 M were 21.6 mg; 24.1 mg; 34.5 mg; 39.4 mg and 62.4 mg respectively. Ferrihydrite produced from electrolysis of KCl 0.4 M concentration was dark red The XRD results show the presence of α-Fe2O3 and PSA results show that the α-Fe2O3 particle size is 151.57-171.25 nm.